Soil preferential flow dynamics in the southern drylands of India—a watershed based approach - Pushpanjali,; Reddy, K. S.; Dhimate, Ashish S.; Karthikeyan, K.; Samuel, Josily; Reddy, A. G. K.; Ravi Kumar, N.; Rao, K. V.; Pankaj, Prabhat Kumar; Rohit, Jagriti; Kumar, Manoranjan; Singh, V. K. (Frontiers in Water, 2025)
Preferential flow refers to the specific pathways through which water flows, including biopores, fractures, and macropores. Soil preferential flow has become increasingly important in the face of changing climates, erratic rainfall patterns, and for effective rainwater management. In semi-arid regions, watersheds serve as fundamental hydrologic units, providing a holistic perspective for the study of soil preferential flow. Given that limited research has been conducted on soil preferential flow in the dryland regions of southern India, the Hayathnagar watershed in Hyderabad was selected for this study. Land uses at different elevations were considered to systematically collect data on soil preferential flow, allowing for an analysis of how variations in elevation and land use influence flow dynamics across the landscape in the watershed. Brilliant blue tracer experiments were conducted at selected sites within the Hayathnagar watershed to assess soil preferential flow and investigate the subsurface movement of water across three land uses (cropped, fallow, and forest) under varying elevations. Vertical profile images were captured using a Canon EOS 1300D digital camera, producing high-resolution images (5184 × 3456 pixels). These digital images were then processed using ArcGIS 10.3 and ImageJ. The presence of preferential flow was clearly evident across all three different land uses and elevations within the watershed. The lower reach, with the least elevation, exhibited the highest dye coverage, correlating with greater uniform infiltration depth values. Furthermore, the middle reach displayed the maximum soil preferential flow, as indicated by the higher preferential flow fraction values, which were further justified by the preferential flow evaluation index. Heterogeneous matrix flow and fingering were observed both at the surface and sub-surface, along with macropore flow with low and mixed interactions. The findings and methodology of this study have significant implications for understanding preferential flow in diverse watersheds across the region. By enhancing our understanding of soil–water dynamics and flow patterns within the soil profile, this research contributes to the development of effective water management strategies in such areas.